Effectiveness of Mid-Day-Meal Scheme in Primary Schools with special reference to Nalbari District, Assam (International Journal of Food and Nutritional Sciences, 2022)
Education plays an essential role in the advancement of human potential. Education acts as an indicator of building human capital. It plays an important role in the socio-economic development of a country. The government of India has made education compulsory for 6 to 14 years of age group children. Lacking basic education, the human mind directs to poverty, hunger, and crime. Against this backdrop, the Indian government has undertaken the Mid-Day Meal Scheme to deal with the most critical problems of society. At present, the scheme is being executed in lower primary and upper primary classes. It is one of the primary initiatives undertaken by the Government of India to accomplish the purpose of universalization of primary education through the provision of nutritious support to primary school children. The study is an attempt to investigate the effectiveness of the Mid-Day-Meal scheme in lower-primary and upper-primary schools of the Nalbari District of Assam.